The Causes of the War of 1812 - Horsman, Reginald (University of Pennsylvania Press, 2016)
The origins of the War of 1812 have long been a source of confusion for historians, owing to the lack of attention that has been paid to England's part in precipitating the conflict and to the overemphasis placed on "western expansionist" factors. This volume offers the first analysis of the causes of the war from both the British and American points of view, showing clearly that, contrary to the popular misconception, the war's basic causes are to. be found not in America but in Europe. For unless one accepts the view that America committed an act of pure aggression in 1812, one must turn to the motives underlying British policy to determine why America felt it had to fight. In the years immediately preceding the war (1803-1812), England was dominated by a faction that pledged itself not only to defeat Napoleon but also to maintain British commercial supremacy. The two main points of contention between England and America during this period--impressment and the restrictions imposed by the Orders in Council--were direct results of these commitments. America finally had no alternative but to oppose with force British maritime policy, which, although partly caused by jealousy of American commercial growth, stemmed in large measure from involvement in total war with France. In addition to tracing the gradual drift to war in America, Reginald Horsman shows that the Indian problem and American expansionist designs against Canada played small part in bringing about the struggle. He examines the efforts made by America to avoid conflict through means of economic coercion, efforts whose failure confronted the nation with two choices: war or submission to England. Since the latter alternative presented more terrors to the recent colonists, America went to war.